Peningkatan Kepuasan Pelanggan melalui Kualitas Produk dan Kualitas Layanan - Permana, Made Virma (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2013)
The aim of this research is to analyze the effect of design quality, product innovation, social competence, technical competence, product quality, service quality to customer satisfaction by developing a research model and proposing six hypotheses. The numbers of samples were 150 respondents. They are the users of Toyota vehicles in Semarang. The technique for analizing the data is Structural Equation Modeling (SEM) from 16.0 AMOS. Based on the results of data analysis, it can be concluded that the model can be well accepted. The results of this study also provide a theoretical implication; it is the influence of design quality variable, product innovation variable, social competence variable, technical competence variable, products quality variable, service quality variable to the variable of consumers satisfaction is positive and significant. The variable that dominantly influences the product quality is design quality and the variable that dominantly influences the service quality is social competence. Finally, service quality becomes the dominant variable that influences customer satisfaction.